INTERNATIONAL COLLABORATION ITDC-DORNA: THE CONTRIBUTION OF MANDALIKA MOTOGP TO SDG 17 - Penti, Nurul; Dermawan, Windy; Lanti, Irman Gurmilang (Pena Cendekia Insani, 2026)
This research focuses on the analysis of the collaboration between the Indonesia Tourism Development Corporation (ITDC) and Dorna Sports in organizing the Mandalika MotoGP as a form of implementation of Transnational Public-Private Partnerships (TPPPs) within the framework of tourism diplomacy and its contribution to the achievement of Sustainable Development Goals (SDG 17) on global partnerships. This research uses a qualitative approach with a case study design, relying on secondary data in the form of official ITDC reports, cooperation documents, policy publications, and relevant academic literature, which are analyzed thematically and interpretatively. The results of the study indicate that the ITDC-Dorna Sports collaboration is built on the basis of a complementary but asymmetrical division of roles, where ITDC plays a dominant role in providing infrastructure, regional governance, and policy coordination, while Dorna Sports has advantages in mastering technical standards, global legitimacy, and international market networks. This collaboration contributes to SDG 17 through three main dimensions, namely capacity building, resource mobilization, and multi-stakeholder governance, but this contribution is limited and faces challenges of imbalanced power relations and limited participation of local communities. The implications of this research confirm that SDG 17 is better understood as an analytical framework for interpreting the dynamics of transnational public–private partnerships in tourism diplomacy, rather than simply a normative indicator of success. These findings provide a conceptual and practical foundation for formulating more inclusive, accountable, and sustainable global partnership policies for organizing international sporting mega-events.